The Social Construction of Religious Moderation in Urban Settings: The Menyama Braya Practice of the Monang Maning Community from the Perspective of Pierre Bourdieu - Maurell Dwinita Annisaputri (Tabéq: Journal of Local Wisdom, Belief, and Peace, 2026)
Religious moderation serves as a crucial mechanism for maintaining social harmony within contexts of religious, ethnic, and cultural diversity. In Bali, a prominent form of religious moderation rooted in local wisdom is Menyama Braya, a philosophy of brotherhood that emphasizes mutual respect and coexistence irrespective of background differences. This study analyses the practice of religious moderation grounded in the local wisdom of Menyama Braya among the Balinese ethnic community in the multicultural village of Monang Maning, Denpasar City. A qualitative approach is employed, utilizing the case study method. Data were collected through observation, in-depth interviews, and documentation. Data analysis applies Pierre Bourdieu’s theory of social practice, with particular attention to the interaction among habitus, capital, and field. The findings demonstrate that the values of Menyama Braya extend beyond cultural discourse and are internalized as habitus, manifested through social traditions such as mutual cooperation, respect for interfaith sites, and tolerance in religious practices. These traditions reinforce social and cultural capital, providing a foundation for sustaining cohesion and harmony among individuals of different faiths in a diverse urban environment.